Norwegian-speaking Sami and Russian-speaking Kazakh young adults: a comparative study of identities - Koshmagambetova, Aikhanym (UiT Norges arktiske universitet, 2023)
In the given thesis, the identities of the Norwegaian-speaking Sami and the Russian-speaking Kazakh young adults are analysed in relation to their first languages' influence on the identity formation. The research is conducted by interviewing 10 representatives of the given groups and applying thematic analysis to the data gathered. The given reserach contributes to understanding how do ethnic minorities with shared colonial past build their identities around their historical experiences and without being able to lean on their native language as a core element of their ethnic identities.